Public provision of business support services in Finland - Lotta Väänänen (The Research Institute of the Finnish Economy (ETLA), 2003)
The Finnish government, in addition to providing finance to SMEs, has established a number of support mechanisms that provide assistance to SMEs via free or subsidized business support services. In this paper, we review the public organisations providing business services, and the instruments used. Using recent survey data on SMEs, we explore what kinds of SMEs use public services, and examine whether firm characteristics differentiate between users of public and private sector services. The appendix to this study presents the survey and the responses to it. We find that there is currently quite extensive service provision by the public sector, which may have both positive and negative implications. For one, it is encouraging to find that Finnish SMEs are supported throughout their growth cycle, and that the public sector organisations have taken an active role in further developing their cooperation to better serve the customers' needs. It is also positive to find that innovative firms are more likely to use public services, and thus there are likely to be some social returns from them due to positive externalities. However, there is also a concern of whether the extensive public sector activity has the effect of crowding out otherwise profitable private business, thus hampering the development of markets for SME consultants and service providers. For this reason, the public sector should put effort into examining where market failures exist and focus its activities where the private sector is not present but which can have positive social returns. Areas where the public sector would seem to have a clear role in service provision are, for example, in collecting and disseminating information, and in coordinating programs that involve networking. – – Sen lisäksi, että Suomen valtio tarjoaa julkista rahoitusta suomalaisille pienille ja keskisuurille (pk-) yrityksille, se tukee niitä myös tarjoamalla niille palveluita. Tässä tutkimuksessa tarkastelemme minkälaiset pk-yritykset käyttävät julkisia liiketoiminnan tukipalveluita sekä tutkimme eroavatko julkisen ja yksityisen sektorin palveluita käyttävät yritykset ominaisuuksiltaan. Tutkimuksen liite sisältää kattavan kuvauksen tehdystä kyselystä sekä sen vastauksista. Selvitys osoittaa, että julkisen sektorin liiketoiminnan tukipalvelujen tarjonta on laajaa, ja sillä on pääosin positiivisia mutta mahdollisesti myös joitain negatiivisia vaikutuksia. Positiivisia havaintoja ovat, että pk-yrityksiä tuetaan läpi niiden elinkaaren ja että julkiset organisaatiot ovat lähteneet kehittämään yhteistyötään vastatakseen niiden tarpeisiin entistäkin paremmin. On myös positiivista havaita, että innovatiiviset yritykset käyttävät julkisia palveluita suuremmalla todennäköisyydellä kuin keskimääräinen pk-yritys, jolloin palvelujen käytöstä voidaan odottaa, ulkoisvaikutusten johdosta, myös yhteiskunnallisia hyötyjä yrityksen saaman hyödyn lisäksi. Huolen aiheita ovat, että laaja julkisen sektorin palvelujen tarjonta saattaa syrjäyttää yksityistä liiketoimintaa ja hidastaa yksityisen sektorin pk-yritysten konsultoinnin ja muun palveluntarjonnan kehitystä. Julkisen sektorin tulisikin ottaa toimintansa lähtökohdaksi markkinapuutteiden selvityksen ja siten rajata omaa rooliansa sellaisiin aktiviteetteihin, joita yksityinen sektori ei tarjoa, mutta joilla voidaan saavuttaa yhteiskunnallista hyötyä. Alueita, joilla julkisella toimijalla näyttäisi olevan selvä rooli ovat esimerkiksi tiedon kerääminen ja levittäminen sekä yritysten verkottumisen tukeminen.
Keywords: 330; Klein- und Mittelunternehmen; Finnland; Wirtschaftsförderung